Glial Activation Enhances Spinal TRPV1 Receptor Sensitivity in a Paclitaxel Model of Neuropathic Pain - Slepicka, J; Palecek, J (Physiological research, 2025)
Paclitaxel (PTX), a commonly used chemotherapeutic, frequently leads to chemotherapy-induced peripheral neuropathy (CIPN), characterized by persistent pain and neuronal hypersensitivity. While its effects on peripheral nerves are well-documented, paclitaxel also influences central nervous system pathways, particularly spinal synaptic transmission, through Toll-like receptor 4 (TLR4) activation and subsequent sensitization of transient receptor potential vanilloid 1 (TRPV1) receptors. In this study, we used an in vitro model of paclitaxel-induced neuropathic pain to investigate the role of glial activation in TRPV1 receptor function. Using whole-cell patch-clamp recordings from superficial dorsal horn neurons in acute spinal cord slices, we evaluated the effects of minocycline (MX), a glial cell inhibitor, and ISO-1, a macrophage migration inhibitory factor (MIF) antagonist, on paclitaxel-induced synaptic changes. Our results demonstrate that acute paclitaxel application enhances nociceptive signaling and impairs capsaicin-induced TRPV1 receptor tachyphylaxis, leading to sustained hyperactivity. Minocycline preincubation effectively mitigated paclitaxel-induced sensitization, restoring normal nociceptive signaling, whereas acute minocycline treatment failed to prevent these changes. ISO-1 in vitro co-incubation with paclitaxel did not affect the paclitaxel-induced changes. These findings offer novel insight into the intricate interactions among neuroinflammatory mediators, glial cell activation, and TRPV1 receptor sensitization in paclitaxel-induced neuropathic pain. The differential effects of acute versus prolonged pre-incubation minocycline application suggest the importance of sustained glial inhibition for effective outcomes and neuropathic pain management.
Keywords: kationtové kanály TRPV; neuroglie; Paclitaxel; modely nemocí na zvířatech; Disease Models, Animal; fytogenní protinádorové látky; neuralgie; Rats; Male; krysa rodu Rattus; Neuroglia; Antineoplastic Agents, Phytogenic; Spinal Cord; TRPV Cation Channels; Rats, Sprague-Dawley; mužské pohlaví; mícha; potkani Sprague-Dawley; Animals; paclitaxel; zvířata; Neuralgia